2019
DOI: 10.1074/jbc.ra118.006741
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of dAKAP1–protein kinase A signaling islands from the outer mitochondrial membrane alters breast cancer cell metabolism and motility

Abstract: Breast cancer screening and new precision therapies have led to improved patient outcomes. Yet, a positive prognosis is less certain when primary tumors metastasize. Metastasis requires a coordinated program of cellular changes that promote increased survival, migration, and energy consumption. These pathways converge on mitochondrial function, where distinct signaling networks of kinases, phosphatases, and metabolic enzymes regulate these processes. The protein kinase A-anchoring protein dAKAP1 compartmentali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 72 publications
(103 reference statements)
4
18
0
Order By: Relevance
“…Moreover, mitochondrial fission resulting from AKAP1 downregulation may increase the efficiency of mitochondrial transportation toward the high energy demanding leading edge of metastatic cells. Thus, reduced AKAP1 expression can be viewed as a biochemical switch toward increased breast cancer metastasis [56]. While this study may appear to be contradictory to studies where increased AKAP1 has been viewed as a "bad" sign for cancer patients, a closer look opens up very fascinating discussions about the dynamic changes adopted by cancer cells when transitioning at different disease stages.…”
Section: Akap1 In Cancer Progression and Treatmentmentioning
confidence: 60%
See 4 more Smart Citations
“…Moreover, mitochondrial fission resulting from AKAP1 downregulation may increase the efficiency of mitochondrial transportation toward the high energy demanding leading edge of metastatic cells. Thus, reduced AKAP1 expression can be viewed as a biochemical switch toward increased breast cancer metastasis [56]. While this study may appear to be contradictory to studies where increased AKAP1 has been viewed as a "bad" sign for cancer patients, a closer look opens up very fascinating discussions about the dynamic changes adopted by cancer cells when transitioning at different disease stages.…”
Section: Akap1 In Cancer Progression and Treatmentmentioning
confidence: 60%
“…Several recent studies have suggested that the role of AKAP1 in cancer is complicated due to the heterogeneous nature of cancer cells in different stages of tumor growth and metastasis. While one study suggested AKAP1 inhibits cancer cell invasiveness [56], other studies have reported a poorer prognosis with higher AKAP1 expression [57,58].…”
Section: Akap1 In Cancer Progression and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations